All-cause and liver-related mortality in HIV positive subjects compared to the general population: Differences by HCV co-infection - Hernando, Victoria; Perez-Cachafeiro, Santiago; Lewden, Charlotte; Gonzalez, Juan; Segura, Ferran; Oteo, Jose Antonio; Rubio, Rafael; Dalmau, David; Moreno, Santiago; Amo, Julia del (Journal of hepatology, 2012)
We aimed at comparing overall and liver-related mortality rates, observed in HIV positive subjects followed-up in the Cohorts of Spanish Network on HIV/AIDS Research stratified by HCV co-infection status, with the expected mortality of the general population of same age and sex in Spain, for the period 1997 – 2008. We estimated standardized mortality ratio (SMR) and excess mortality, comparing death rates from our cohort (globally and by HCV co-infection) with death rates from the general population standardized by sex in 5year-age bands. Overall, 5914 HIV positive subjects were included, 37.3% of which were co-infected with HCV; 231 deaths occurred, 10.4% of which were liver-related. SMR for all causes mortality for the HIV positive subjects was 5.6 (CI 95% 4.9–6.4), 2.4 (1.9–3.1) for HCV negative subjects and 11.5 (9.9–13.4) for HCV positive ones. Having HCV co-infection and AIDS yielded an SMR of 20.8 (16.5–26.1) and having AIDS and being HCV negative had an SMR of 4.8 (3.5–6.7). SMR for liver-related mortality was 1.8 (0.6–5.7) for HCV negative subjects vs. 22.4 (14.6–34.3) for HCV positive ones. Overall, both mortality rates as SMR and excess mortality rates were higher for injecting drug users (IDUs) than men having sex with men (MSM) and heterosexuals, patients with AIDS, with and without cART and for subjects included between 1997 and 2003. There was an excess of all-cause and liver-related mortality in our cohorts compared with the general population. Furthermore, HCV co-infection in HIV positive patients increased the risk of death for both all causes and liver-related causes.